Biorefining of Biomass to Biofuels Opportunities and Perception (Biofuel and Biorefinery Technologies,, 2018)
This volume focuses on the prospects of the conversion of biomass into biofuels including ethanol, butanol, biogas, biohydrogen, biodiesel, syn-gas and other useful products. Biomass-derived fuels have gained tremendous attention worldwide. However, due to high raw material and processing costs, biofuels produced from lignocelluloses have been found to be more expensive than conventional fuels. Therefore, a concept of biorefining has been introduced, where more than one product or each and every component of biomass may be derived into useful products in a manner of petroleum refinery.